Efektivitas Penggunaan Lisensi “Es Teh Indonesia” Pada Penjualan Di Outlet Es Teh Indonesia Cabang Kota Kendari Perspektif Maqashid Syari’ah - Kurniawan, Muhammad Syamikh Abdillah Kurniawan; Ridha, Ahmad (Fawaid : Sharia Economic Law Review, 2025)
This study analyzes the effectiveness of the “Es Teh Indonesia” licensing system at the Kendari branch outlets from the perspective of Maqashid al-Shariah, particularly the principle of hifz al-mal (protection of wealth). The research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews with outlet owners and employees, as well as documentation. The data were analyzed inductively, with validity ensured through triangulation of sources, techniques, and time. The findings indicate that the implementation of the license significantly contributes to increased sales, expanded customer base, and improved operational standards through standardized procedures and brand strength. From the Maqashid al-Shariah perspective, the license partially fulfills the principle of wealth protection by safeguarding business assets, maintaining product quality consistency, and utilizing brand equity. However, aspects such as fair profit distribution and sustainable operational support still need optimization to achieve comprehensive maslahah (benefit). The study concludes that the effectiveness of a license is not solely determined by contractual compliance but also by the application of Islamic business ethics that balance rights and obligations. Recommendations include enhancing business literacy among licensees, promoting operational and financial transparency, and ensuring continuous support from the franchisor to strengthen business sustainability.   Kata Kunci: Lisensi, Waralaba, Es Teh Indonesia, Efektivitas, Maqashid Syari’ah, Hifz al-Mal